2019
DOI: 10.1186/s12931-019-1008-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of residual SYNTAX score in patients with obstructive sleep apnea and acute coronary syndrome: a prospective cohort study

Abstract: Background There is a paucity of data from large prospective study evaluating the prognostic significance of the residual Synergy between percutaneous intervention with Taxus drug-eluting stents and cardiac surgery (SYNTAX) Score (rSS) in patients with obstructive sleep apnea (OSA) and Acute Coronary Syndrome (ACS). Methods ACS patients who undergoing percutaneous coronary angiography and completing a sleep study during hospitalization were prospectively enrolled. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…We recommend that all patients with MVCAD undergoing PCI should undergo a functional assessment of the residual lesions even though they appear as anatomically significant that would translate into good clinical outcomes, which was proved in chronic kidney disease as well as obstructive sleep apnea patients also. 36 However, further studies are needed to assess the anatomic versus the functional residual burden of residual coronary atherosclerosis that further helps in prognostication.…”
Section: Discussionmentioning
confidence: 99%
“…We recommend that all patients with MVCAD undergoing PCI should undergo a functional assessment of the residual lesions even though they appear as anatomically significant that would translate into good clinical outcomes, which was proved in chronic kidney disease as well as obstructive sleep apnea patients also. 36 However, further studies are needed to assess the anatomic versus the functional residual burden of residual coronary atherosclerosis that further helps in prognostication.…”
Section: Discussionmentioning
confidence: 99%
“…According to the syntax score, the patients were assigned into three groups: high-risk group (syntax score > 32), intermediaterisk group (syntax score of 22 to 32), and low-risk group (syntax score < 22). Involved vessels, including the left anterior descending artery, Right Coronary Artery (RCA), Left Circumflex Artery (LCX), and the left main stem, were also determined (6,18,19). This study was approved by the Ethics Committee of Guilan University of Medical Sciences (no.IR.GUMS.REC.1397.388).…”
Section: Methodsmentioning
confidence: 99%
“…The SYNTAX (Synergy Between Percutaneous Coronary Intervention with Taxus and Cardiac Surgery) score is a grading system to evaluate the complexity and prognosis of patients undergoing percutaneous coronary intervention (6). It is a tool to select revascularization strategies and is obtained based on 11 angiography variables that consider the location and properties of lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Sixteen studies reported an increased Hazard ratio (HR) of MACCEs outcomes with SDB compared with controls in patients with myocardial ischemia, 12,13,16,18,19,20,21,22,23,24,25,26,27,28,29,30 with the combined HR of 1.66(95% CI 1.41-1.94, P< 0.0001) (Fig 2). Some evidence of statistical heterogeneity (Cochran Q = 23.00, p=0.08; I 2 = 35%) was found by pooled effect size, which might be in part attributable to 1 randomized controlled trial.…”
Section: Major Adverse Cardiovascular or Cerebrovascular Events (Macces)mentioning
confidence: 99%